Enhancing the Role of ISO/IEC 17025:2017 Accredited Laboratories in Supporting Tri Dharma Perguruan Tinggi at Geological Engineering Department of UPN “Veteran” Yogyakarta - Rahmad, RM Basuki; Pratomo, Septyo Uji; Haty, Intan Paramita; Istiana, Istiana; Pambudi, Setia (RSF Conference Series: Business, Management and Social Sciences, 2025)
Laboratories play a crucial role in supporting the Tri Dharma Perguruan Tinggi, education, research, and community service in Indonesian higher education institutions. Accreditation under ISO/IEC 17025:2017 provides international recognition of laboratory competence, impartiality, and operational consistency. However, accreditation status alone does not automatically ensure optimal utilization of laboratory resources. This study examines the case of two accredited laboratories, the Optical Mineralogy and Petrology Laboratory and the Micropaleontology Laboratory at the Department of Geological Engineering, Universitas Pembangunan Nasional “Veteran” Yogyakarta. Using a mixed-methods approach, the research relied on primary data from direct observations, training and certification records, and internal quality audits, complemented by secondary documentation, including standard operating procedures, calibration certificates, and utilization reports. Data were analyzed through thematic analysis, descriptive statistics, and gap and SWOT frameworks to evaluate laboratory performance. Findings reveal that accreditation has strengthened organizational structures, enhanced staff competencies, and improved technical reliability. Nevertheless, several challenges remain, including overlapping responsibilities between quality and administrative management, the need for regular refresher training, inconsistent calibration schedules, and overly complex organizational structures. To address these issues, the study proposes strategies such as targeted recruitment, annual calibration programs with digital monitoring, organizational streamlining, and enhanced internal audits. The study concludes that ISO/IEC 17025:2017 accreditation, when combined with systematic optimization, can significantly enhance the role of laboratories in higher education by ensuring the credibility of teaching, research, and community services. Further research should include comparative and longitudinal studies, as well as exploration of digital quality management systems and industry partnerships to maximize the long-term impact of accredited laboratories.